Prolonged infusion of β-lactam antibiotics decreases short-term mortality in critically ill patients: A meta-analysis and trial sequential analysis from randomized control trials - Baofang Liang; Jianwei Su; Ya Wang; Linxin Chen; Yuanchun Mo; Baocheng Xie (Journal of Global Antimicrobial Resistance)
ABSTRACT: Objectives: The aim of this study was to ascertain the clinical efficacy of prolonged infusion of β-lactam antibiotics in critically ill patients and to provide additional evidence. Methods: This meta-analysis was prospectively registered on the PROSPERO database (CRD42024614894). We searched PubMed, Web of Science, Scopus, and Clinical Trials.gov to identify eligible randomized control trials (RCTs) for conducting a meta-analysis and trial sequential analysis (TSA) comparing mortality between prolonged vs. intermittent infusion of β-lactam antibiotics in adult critically ill patients. The Grading of Recommendations Assessment, Development, and Evaluation approach (GRADE) was used to evaluate the certainty of evidence for all outcomes. Results: Twenty-four RCTs involving 9558 adult critically ill patients were finally included in this meta-analysis. Compared with intermittent infusion of β-lactam antibiotics, the pooled results demonstrated that prolonged infusion was associated with lower short-term mortality (OR = 0.87, 95% confidence interval [CI] = 0.79–0.95; high certainty), but not 90-d mortality statistically (OR = 0.91, 95% CI = 0.83–1.01; moderate certainty), which was supported by TSA. Regression analysis found no significant factors affecting short-term mortality. For other outcomes, prolonged infusion could significantly improve clinical cure (OR = 1.31, 95% CI = 1.20–1.42; low certainty) and microbiological eradication (OR = 2.29, 95% CI = 1.61–3.25; moderate certainty). Conclusions: Despite no benefit in 90-d mortality statistically, prolonged infusion of β-lactam antibiotics was associated with significant benefits in short-term mortality, clinical cure, and microbiological eradication. TSA supported the short-term survival benefit of prolonged infusion in critically ill patients.